Pelatihan Pemanfaatan Limbah Organik dari Buah-buahan dan Sayuran Sebagai Bahan Baku Pembuatan Eco Enzyme - Marjenah; Husien, Nani; Handayani, Sri Asih; Rosamah, Enih; Jufriah; Hastaniah (Fakultas Kehutanan dan Lingkungan Tropis, Universitas Mulawarman, 2024)
People have a significant need to consume fruits in daily life. Overall, the pulp of the fruit is the only part that is utilized; thus far, fruit rind is rarely utilized and is merely wasted. Similarly, whenever it relates to vegetables, only the desirable sections are picked; the tougher sections, such as the stems, are usually eliminated. Potential raw materials for the production of eco enzyme (which can be used as liquid organic fertilizer) abounds in the profusion of fruit and vegetable waste. Typically, organic waste is neglected, resulting in an offensive odor that affects the environment's cleanliness and may pose health risks. In an attempt to mitigate the adverse effects caused by organic waste, alternative raw materials for the production of liquid organic fertilizer and eco-enzymes may be derived from fruit and vegetable peel waste. The production process of eco enzyme commences with the segregation of organic waste, which will serve as its main material. Subsequently, blend the components in the suggested proportions (1 part sugar/molasses to 3 parts organic matter to 10 parts water). Three months after the mixture is complete, eco-enzymes may be harvested. The collaborators of this community service endeavor consist of housewives, beverage vendors, and organic waste-focused community organizations. Encouraging economic and social autonomy in the community is the objective of this Community Service Program activity, to educate and raise awareness among the general public regarding the proper disposal of organic garbage in order to create a more sanitary and habitable environment and a greener planet, enhance both soft and physical skills while fostering greater social harmony and comfort.